(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Introduction: In world more than 40 million people are living with HIV/AIDS, 2.3 million are under 15 yrs and 14000 new infections occur daily. The objectives of this study was to assess the lifestyle pattern among the people living with AIDS (PLWA) receiving anti-retroviral therapy at B. P. Koirala Institute of Health Sciences and find out the association between lifestyle pattern and the selected demographic variables. Methodology: A descriptive cross-sectional research design was used to assess lifestyle pattern of the PLWA receiving anti-retroviral therapy at the ART clinic of Tropical ward at B.P Koirala Institute of Health Sciences (BPKIHS). The PLWA receiving ART at BPKIHS for more than or equal to three months at the ART clinic who met the selection criteria constituted the sample of the study. Using purposive sampling technique total 113 PLWA were selected. The patients who themselves were physically present during the data collection period were included in the study, after their consent for the purpose. Results: It was found that most of the PLWA were of age less than 40 years, male (61.1%), residing in urban area (74.3%), married (75.2%) and Hindu (74.3%). It was found that 83.2% PLWA never do exercise, whereas 8.8% perform regularly. Most of the (91.2%) people living with AIDS reported feeling pressure and stress in daily life. About 57% PLWA only sleep less than 6 hours per day. About half (52.2%) of the PLWA never take food outside home, where as 34.5% take food outside regularly. The habit of using tobacco is present among 28.3% people living with ADIS, where the past history of using was 39.8%. Similarly only 0.9% PLWA had habit of taking alcohol at present and 63.7% in past; and 28.3% had habit of taking substances in past. The association calculated between selected demographic variables (age, sex, marital status, residence and religion) with lifestyle pattern (exercise, tobacco chewing, alcohol consumption, and food habit) found significant association between marital status and exercise (p <0.001), Tobacco consumption and age (p <0.001) only. Conclusion: The positive life style practices among the PLWA found high at present in comparison to past especially in relation to Tobacco, Alcohol and Substance use. Individual counseling and support is vital for improving the condition. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12436 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2) 29, Page: 29-33